Mansfield Park and Political Theology. Issue 7 (3rd October 2018) - During, Simon; O'Connell, Lisa
ABSTRACT: This essay examines Jane Austen's Mansfield Park in the light of classical understandings of political theology. It does so by placing the novel in its Anglican and Erastian contexts as well as by showing that it belongs to a lineage of English prose fiction, whose famous names are Samuel Richardson and Henry Fielding, which also had theopolitical interests.